Biventricular repair after the hybrid Norwood procedure. (8th February 2019) - Sojak, Vladimir; Bokenkamp, Regina; Kuipers, Irene; Schneider, Adriaan; Hazekamp, Mark
Abstract: OBJECTIVES: We analysed the outcomes of patients undergoing biventricular repair (BVR) after an initial hybrid Norwood approach as a salvage procedure in extremely sick infants; or as the initial palliation in patients with uncertain feasibility of single-stage BVR due to severe left ventricular outflow tract obstruction; or as part of a left ventricle (LV) recruitment strategy in patients with borderline LVs. METHODS: Between September 2010 and July 2018, 26 patients underwent BVR after initial hybrid palliation at a median age of 13 days. The rationale for the hybrid approach was to promote the growth of the LV in 10 patients and that of the left ventricular outflow tract and/or aortic valve in 12 patients and to be a salvage procedure in 4 patients. Significant growth of the LV was noted during the interstage period, which had a median length of 65 days ( P = 0.008). Fourteen patients underwent aortic arch repair, ventricular septal defect closure and relief of subaortic stenosis; 5 patients underwent the Yasui procedure; 4 patients had the Ross–Konno procedure; 2 patients had an arterial switch operation; and 1 patient had truncus arteriosus repair. RESULTS: Twenty-two patients (84.6%) are alive at a median follow-up period of 1.8 (range 0.04–6.2) years. There were 2 early and 2 late deaths. Nineteen catheter-based reinterventions and 15 reoperations were performed after BVR. CONCLUSIONS: The hybrid Norwood procedure permits stabilization of critical infants. It allows for growth of left ventricular structures in some patients with borderline left hearts and in those with severe left ventricular outflow tract obstruction. More patients may eventually have BVR than was thought during the newborn period.